2017
DOI: 10.4025/actascitechnol.v39i4.29458
|View full text |Cite
|
Sign up to set email alerts
|

<b>Analysis of lubricant oil contamination and degradation and wear of a biogas-fed otto cycle engine

Abstract: ABSTRACT. The increasing deployment of biodigesters for the treatment of waste on farms and the use of the biogas generated in the production of energy have highlighted the need for knowing the influence of this fuel on internal combustion engines. This study aimed to analyze the influence of filtrated biogas on lubricant oil contamination and degradation, as well as on engine wear and corrosion. Lubricant oil samples were collected every 75 engine operating hours (EOH) and then correlated between each other a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 9 publications
0
5
0
1
Order By: Relevance
“…Therefore, it is necessary to remove H 2 S from the biogas and/or to keep its content as low as possible. The most common methods of H 2 S removal include adsorption on activated carbon and the addition of air to biogas [29,30].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it is necessary to remove H 2 S from the biogas and/or to keep its content as low as possible. The most common methods of H 2 S removal include adsorption on activated carbon and the addition of air to biogas [29,30].…”
Section: Resultsmentioning
confidence: 99%
“…The lubricating oil total acid number (TAN) and flash point remained relatively stable across the 5+ years, it can thus be concluded that shearing due to the consistent high temperature operation of the lube oil is most likely responsible for the depletion of oil additives such as Zinc and Magnesium additives which dropped by 23.9% and 26% respectively after 47,520 equivalent operating hours (EOH) leading to the decay in the viscosity. The Magnesium elemental additive decreased by more than the 25% limit earmarked by ASTM D4378 and D5185` [38] for precautionary action to be undertaken ,while both additives depreciated by more than the 20% of new oil concentration for Zinc, Calcium and phosphorus suggested by Ngele et al, (2013) as reported by [39]. The conclusion that shearing is responsible for the decay in viscosity is based on the parameter trends and indicators which conform with assertions made by [40][41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…P a g e | 207 Revista Ibero-Americana de Ciências Ambientais v.10 -n.2  Fev a Mar 2019 periódico. Esse movimento é transformado em movimento rotativo e ligado ao eixo do gerador (BERTINATTO et al, 2017).…”
Section: Sistemas De Aproveitamento Elétricounclassified